Prevalence of the use of antihypertensive medications in Greenland: a study of quality of care amongst patients treated with antihypertensive drugs - Maria Bundgaard; Dorte Ejg Jarbøl; Maja Skov Paulsen; Jytte Lindskov Jacobsen; Michael Lynge Pedersen (International Journal of Circumpolar Health, 2012)
Objectives. The primary objective was to estimate the prevalence of patients diagnosed with hypertension using the proxy marker of antihypertensive drug therapy in Greenland and to compare the prevalences within the 5 health regions in Greenland. The second objective was to review 2 quality indicators in antihypertensive care. Study design. Observational and cross-sectional study reviewing electronic medical records. Methods. Information about age and gender was collected from all patients receiving antihypertensive drug prescriptions within a 2-year period prior to the data extraction in January 2011. Only patients aged 20 or above were included. The age- and gender-specific prevalence of patients in antihypertensive treatment was calculated using the population as it was 1 January 2010 in Greenland as background population. A subsample consisting of patients in antihypertensive treatment aged 20 or above born within the first 5 days of each month was identified. Review of electronic medical records 1 year back in time (1 January 2010 onwards) was carried out and information on blood pressure obtained. The quality of care was evaluated with respect to 2 indicators: follow-up management and blood pressure level, respectively. Results. The total number of patients in treatment with antihypertensive drugs was 4,462 (1,998 males and 2,464 females) corresponding to a prevalence of 11.4% (4,462/39,231). The prevalence was higher among females than among males. The prevalence increased with age and differed among the 5 health regions. The percentage of patients in antihypertensive treatment with minimum 1 follow-up visit within 1 year (blood pressure measured and registered in a health clinic) was only 77.7%. Some 45% of patients in antihypertensive treatment achieved blood pressure below 140/90 mmHg. Conclusion. Hypertension is a common disorder in Greenland. The quality of antihypertensive care is suboptimal and leaves room for improvement. A national strategy based on guidelines, use of electronic drug prescriptions and recording of blood pressures combined with continuous monitoring the quality is recommended in order to prevent complications of untreated hypertension.